2014
DOI: 10.1016/j.cell.2014.08.029
|View full text |Cite|
|
Sign up to set email alerts
|

Resetting Transcription Factor Control Circuitry toward Ground-State Pluripotency in Human

Abstract: SummaryCurrent human pluripotent stem cells lack the transcription factor circuitry that governs the ground state of mouse embryonic stem cells (ESC). Here, we report that short-term expression of two components, NANOG and KLF2, is sufficient to ignite other elements of the network and reset the human pluripotent state. Inhibition of ERK and protein kinase C sustains a transgene-independent rewired state. Reset cells self-renew continuously without ERK signaling, are phenotypically stable, and are karyotypical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

56
928
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 817 publications
(1,016 citation statements)
references
References 67 publications
56
928
3
Order By: Relevance
“…Previous studies demonstrated that human and mouse naïve PSCs contain mitochondria with more immature morphology than primed PSCs (Zhou et al, 2012). At the same time, human and mouse naïve PSCs exhibit increased OXPHOS (Takashima et al, 2014;Zhou et al, 2012). Now Gu et al (2016) demonstrate that human naïve PSCs, both newly derived and those cultured in previously reported reversion conditions (Takashima et al, 2014;Theunissen et al, 2014), in addition to higher mitochondrial oxygen consumption also display elevated glycolytic rates.…”
Section: Main Textmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies demonstrated that human and mouse naïve PSCs contain mitochondria with more immature morphology than primed PSCs (Zhou et al, 2012). At the same time, human and mouse naïve PSCs exhibit increased OXPHOS (Takashima et al, 2014;Zhou et al, 2012). Now Gu et al (2016) demonstrate that human naïve PSCs, both newly derived and those cultured in previously reported reversion conditions (Takashima et al, 2014;Theunissen et al, 2014), in addition to higher mitochondrial oxygen consumption also display elevated glycolytic rates.…”
Section: Main Textmentioning
confidence: 99%
“…At the same time, human and mouse naïve PSCs exhibit increased OXPHOS (Takashima et al, 2014;Zhou et al, 2012). Now Gu et al (2016) demonstrate that human naïve PSCs, both newly derived and those cultured in previously reported reversion conditions (Takashima et al, 2014;Theunissen et al, 2014), in addition to higher mitochondrial oxygen consumption also display elevated glycolytic rates. Human naïve PSCs consumed more glucose, produced more lactate, and incorporated more glucose carbons into lactate and into purine and pyrimidine nucleotides, implying increased flux towards glycolysis and the PPP.…”
Section: Main Textmentioning
confidence: 99%
See 3 more Smart Citations